2002
DOI: 10.1128/aac.46.3.762-768.2002
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of Herpes Simplex Viruses to Penciclovir and Acyclovir in Eight Cell Lines

Abstract: The commonly used antiviral drugs acyclovir (ACV) and penciclovir (PCV) possess similarly potent antiviral activities in vivo against herpes simplex virus (HSV). Assay methods for sensitivity to ACV are not necessarily transferable to PCV, even though the two drugs have similar in vivo potencies and mechanisms of action. We determined by plaque reduction assay the relative activities of ACV and PCV against five laboratory-adapted strains of HSV types 1 and 2 (including sensitive and resistant strains) in seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 31 publications
(24 reference statements)
6
20
0
Order By: Relevance
“…Antiviral assays in monolayers of PHKs, showed that IC 50 values obtained in PHKs were higher than those we have previously reported for human embryonic fibroblasts. Differences in drug susceptibility profiles for HSV among different cell lines have been reported previously (1,7,13). ACV, BVDU, PCV, and GCV depend on phosphorylation by the viral TK for their activation; therefore, when ACV, PCV, and on May 9, 2018 by guest http://aac.asm.org/ BVDU were tested in the organotypic epithelial raft culture system, they proved active only against TK ϩ strains, while PFA and CDV, which do not require phosphorylation by the viral TK, proved active against both TK ϩ and TK Ϫ strains.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral assays in monolayers of PHKs, showed that IC 50 values obtained in PHKs were higher than those we have previously reported for human embryonic fibroblasts. Differences in drug susceptibility profiles for HSV among different cell lines have been reported previously (1,7,13). ACV, BVDU, PCV, and GCV depend on phosphorylation by the viral TK for their activation; therefore, when ACV, PCV, and on May 9, 2018 by guest http://aac.asm.org/ BVDU were tested in the organotypic epithelial raft culture system, they proved active only against TK ϩ strains, while PFA and CDV, which do not require phosphorylation by the viral TK, proved active against both TK ϩ and TK Ϫ strains.…”
Section: Discussionmentioning
confidence: 99%
“…EC 50 was an unknown fitting parameter in all simulations. While EC 50 values are roughly similar for ACV and FCV, estimates based on the results of plaque reduction assays are reliable only for resistant isolates with EC 50 s of Ͼ2 g/ml (8.9 M ACV and 6.2 M FCV): estimates vary by 1 to 2 log units between cell lines for sensitive isolates (20). Moreover, the conditions used for these cell culture-based assays may or may not represent in vivo infection.…”
Section: Fig 1 Mathematical Model (A)mentioning
confidence: 99%
“…Second, we performed global sensitivity analyses of PK/PD parameters to explore which PK/PD values are most likely to impact clinical outcomes. All model parameters (C max , T max , and EC 50 ) were randomly drawn from probability distribution functions (pdf's), which were derived according to a literature review (15,19,20). The Hill coefficient was randomly selected for values between 1 and 2.…”
Section: Fig 1 Mathematical Model (A)mentioning
confidence: 99%
“…Cytotoxicity assay. The cytotoxicity of the drug for mammalian cells was measured by the neutral red uptake assay (26) with mouse peritoneal macrophages and a transformed cell line (Vero cells) (29). The cells were cultivated in 96-well microtiter plates (150 l containing 10 5 cells/ml in Eagle minimal essential medium [Eagle MEM]/well) at 37°C in a humidified 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%